A systems approach to organisational change leading to world class manufacturing - Christopher, Alan Fred (Department of Mechanical Engineering, 2014)
The author has reviewed World Class Manufacturing and considered the traditional ways of embarking on world class manufacturing initiatives. The reason for the failure of many of these initiatives has been argued. From a systems theory of organisations and the theory of levels of existence, a systemic process to becoming a world class manufacturing organisation has been postulated. This process has been formulated into a Coping Development model. A critique of the model has been included. The critique discusses obstructions to development and draws conclusions regarding the models application.